The Impact of Cognitive Distortions on Decision Making in Agile Project Management Frameworks: Current Positions and Perspectives in the Academic Community - D. A. Khamitov (Управленческие науки, 2024)
The purpose of the study is to review the current positions and views of the scientific community regarding the influence of cognitive distortions (both individual and group) on decision-making within such an approach to project management as agile framework. The article defines the concepts of “project”, “project management”, “agile project management framework”, “heuristics”, “cognitive distortions”; it describes what kind of decisions (according to the hierarchical structure) can be made when using agile project management frameworks. On the basis of analysis of a number of scientific works, the existence of the problem of success (efficiency) of implemented (including IT) projects even if modern flexible frameworks of project management are used is fixed. The author of the study considers the concept of heuristics and cognitive distortions (both individual and group), describes the manifestation of individual and group cognitive biases, gives examples of individual and group cognitive biases’ impact to decisions taken in Agile project management. As a result, the author proposes a classification of likely to manifest individual and group cognitive biases at each of the three levels of decision-making in Agile (according to the hierarchical structure): operational decisions, tactical decisions, strategic decisions. The author also provides an overview of the development of decision-making theory and describes three main approaches to the consideration of the empirical decision-making process: according to D. Kahneman and A. Tversky (heuristic approach; behavioral economics), according to G. Gigerenzer (ecological rationality approach), according to G. Klein (naturalistic approach). The author also identifies a possible further vector for the development of research in this direction. The result of the work was the classification of probable individual and group cognitive distortions at each of the three levels of decision-making in flexible project management frameworks (according to the hierarchical structure): operational, tactical, and strategic.